THE ONLINE SINGLE SUBMISSION POLICY OF THE LOCAL GOVERNMENT APARATURE IN THE ERA OF GLOBALIZATION - Prijo Dwi Atmanto (Jurnal Pembaharuan Hukum, 2019)
The Electronic Integrated Business Licensing Service, which is more easily referred to by the generic name Online Single Submission, is present in the context of business licensing services that apply in all Ministries, Institutions and Local Governments throughout Indonesia, which so far have been carried out through Pelayanan Terpadu Satu Pintu (PTSP). Apart from PTSP, the public can access the OSS System online wherever and whenever. The OSS system was built in the context of accelerating and increasing investment and business, by applying licensing to seek to be integrated electronically. In the latest regulation regarding OSS, namely Government Regulation Number 24 of 2018, the Government regulates among other things the types, applicants, and issuance of businesspermits; implementation of business licensing; business licensing reforms by sector, OSS system, OSS institutions, OSS funding; incentives or disincentives for business licensing through OSS; problem-solving and business obstacles; and sanctions.